mgm : José Morales. Sara De Giles. Juan González Mariscal (2007)
Breve biografía de los integrantes del estudio y datos técnicos de las obras presentadas en este número.
Keywords: MGM ARQUITECTOS; MORALES SÁNCHEZ, JOSÉ; GONZÁLEZ MARISCAL, JUAN; GILES DUBOIS, SARA DE; ARQUITECTURA; ESTUDIOS DE ARQUITECTURA; ESPAÑA